A linear regression-based delay-bounded multicast protocol for vehicular ad hoc networks. (2016) - Juang, Tong-Ying; Cheng, Jo-Chen
Vehicles may inform emergent events or car accidents by using a routing protocol in vehicular ad-hoc networks (VANETs). Many researches focus on minimising the end-to-end delay instead of reducing the usage of radio. Recently, delay bounded routing protocol is designed for minimising the usage of radio within user-defined delay time. In this paper, we focus on linear regression-based delay-bounded multicast, whose goal is to deliver messages to many destination regions within user-defined delay of each region by minimising the usage of radio. In our protocol, the message can be delivered to the destination regions by the hybrid of data mulling, which carried by a vehicle, when the available time is enough and the other forwarding, which delivered through radio. There are two schemes the greedy and the centralised in our protocol. Simulation results show that the proposed multicasts protocol performs better than existed research in terms of total transmitted bytes.